2010
DOI: 10.1080/13658810903401008
|View full text |Cite
|
Sign up to set email alerts
|

Area aggregation in map generalisation by mixed-integer programming

Abstract: Topographic databases normally contain areas of different land cover classes, commonly defining a planar partition, that is, gaps and overlaps are not allowed. When reducing the scale of such a database, some areas become too small for representation and need to be aggregated. This unintentionally but unavoidably results in changes of classes. In this article we present an optimisation method for the aggregation problem. This method aims to minimise changes of classes and to create compact shapes, subject to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…Aggregation with displacement displaces the set of objects until they touch or overlap and then subsequently merges these objects [54]. If the objects in question initially touch no displacement is necessary and they can be simply merged [48,49]. Aggregation by flooding replaces the set of objects in question with a single object of greater spatial extent such as the convex hull.…”
Section: Map Generalisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregation with displacement displaces the set of objects until they touch or overlap and then subsequently merges these objects [54]. If the objects in question initially touch no displacement is necessary and they can be simply merged [48,49]. Aggregation by flooding replaces the set of objects in question with a single object of greater spatial extent such as the convex hull.…”
Section: Map Generalisationmentioning
confidence: 99%
“…Semantic constraints ensure generalization is performed in a manner which is a function of object semantics. Kieler et al [48] and Haunert and Wolff [49] propose aggregation techniques which ensure that objects merged predominantly belong to the same class. Metric constraints perform generalization in a manner which is a function of an error function.…”
Section: Map Generalisationmentioning
confidence: 99%
“…For the aggregation of areas in map generalization, we [35] developed an ILP-based method and presented a comparison with an approach based on simulated annealing. Since the exact ILP-based method could not solve large problem instances, it was combined with a heuristic decomposition technique.…”
Section: Related Workmentioning
confidence: 99%
“…Usually, every output area must have at least a certain minimal size. Subject to this requirement, Haunert and Wolff [12] suggested minimizing a cost function that combines two objectives: the overall weighted class change should be small and the resulting areas should be geometrically compact. They showed that the problem is NP-hard and developed an exact method based on integer linear programming and a heuristic method based on simulated annealing.…”
Section: Area Aggregationmentioning
confidence: 99%